Effect of sowing density on the vegetative development of aguaje (Mauritia flexuosa L.f.) in forest plantations - Freitas Alvarado, Luis (2019)
In this work, the effect of two planting distances of Mauritia flexuosa on its height is studied, quantified the sex ratio and ecological requirements needed by the species, e.g. light and crown shape. We conducted this study in two plots, each one with a different planting distance, which were monitored throughout 6 years starting after 6 years of the establishment of the plantations. Increased planting distance in between individuals gave increased average height and thus increased growth. Individuals planted with higher vs lower distances grew in average 15.28 m and 13.1 m in height respectively. The proportion of fertile palms increased throughout time and was lower in plantations with higher palm densities. The presence of female individuals increased also with time. There was a strong competition among palm crowns related to light requirements in good and acceptable categories. We recommended to continue with the evaluation and future analysis of this species’ behavior.